The functional significance of redox-mediated intersubunit cross-linking in regulation of human type 2 ryanodine receptor - Nikolaienko, Roman (Redox Biol, 2020)
The type 2 ryanodine receptor (RyR2) plays a key role in the cardiac intracellular calcium (Ca(2+)) regulation. We have previously shown that oxidative stress activates RyR2 in rabbit cardiomyocytes by promoting the formation of disulfide bonds between neighboring RyR2 subunits. However, the functional significance of this redox modification for human RyR2 (hRyR2) remains largely unknown. Here, we studied the redox regulation of hRyR2 in HEK293 cells transiently expressing the ryr2 gene. Analysis of hRyR2 cross-linking and of the redox-GFP readout response to diamide oxidation revealed that hRyR2 cysteines involved in the intersubunit cross-linking are highly sensitive to oxidative stress. In parallel experiments, the effect of diamide on endoplasmic reticulum (ER) Ca(2+) release was studied in cells co-transfected with hRyR2, ER Ca(2+) pump (SERCA2a) and the ER-targeted Ca(2+) sensor R-CEPIA1er. Expression of hRyR2 and SERCA2a produced “cardiac-like” Ca(2+) waves due to spontaneous hRyR2 activation. Incubation with diamide caused a fast decline of the luminal ER Ca(2+) (or ER Ca(2+) load) followed by the cessation of Ca(2+) waves. The maximal effect of diamide on ER Ca(2+) load and Ca(2+) waves positively correlates with the maximum level of hRyR2 cross-linking, indicating a functional significance of this redox modification. Furthermore, the level of hRyR2 cross-linking positively correlates with the degree of calmodulin (CaM) dissociation from the hRyR2 complex. In skeletal muscle RyR (RyR1), cysteine 3635 (C3635) is viewed as dominantly responsible for the redox regulation of the channel. Here, we showed that the corresponding cysteine 3602 (C3602) in hRyR2 does not participate in intersubunit cross-linking and plays a limited role in the hRyR2 regulation by CaM during oxidative stress. Collectively, these results suggest that redox-mediated intersubunit cross-linking is an important regulator of hRyR2 function under pathological conditions associated with oxidative stress.